Students’ Responses toward The Implementation of Paraphrasing Technique in English Poetry Class - Utami, I.G.A. Lokita Purnamika (Jurnal Pendidikan dan Pengajaran, 2014)
This article aimed at describing the students’ responses toward the paraphra-sing technique implemented in an English poetry class. This article developed from an action research conducted at two Poetry classes in the academic year of 2012/2013 in English Education Department of UNDISHA. The results indicated that the students responded positively toward the implementation of the technique, especially in four aspects, i.e. (1) it involved their active participation; (2) it could solve problems caused by the language deviation; (3) it could increase the students’ sensitivity in interpreting culture, symbol and figurative language used in poetry; (4) it also improved the students understanding of some language components, such as vocabulary and grammar. The students’ positive responses were also followed by their improvement in under-standing English language poems. Keywords: english poems, paraphrasing technique, students’ responses